The Teachers’ Teaching Strategies In Facing Students’ Different Learning Style In SMPN 1 Lembang Jaya - Itrawati, Itrawati; Sari, Mezia Kemala; Yoni, Efri (FKIP UMSB, 2024)
This research was aimed to find out the teachers’ teaching strategies in facing students different learning styles. The design of research was descriptive. The subject of the research was the 30 students from three classes (VII.2, VIII.2 and VIII.3) and 3 English teachers in SMPN 1 Lembang Jaya. Instruments used to collect the data in this research were questionnaire and study of lesson plan. The questionnaire used to analyze students learning styles, and study of lesson plan used to analyze teachers teaching strategy. From the result of the research, the research found that students has three learning styles (visual style, auditory style and kinesthetic style), from the three learning styles above in SMPN 1 Lembang Jaya, visual learner as dominant students learning styles. Furthermore, as for teachers teaching strategy the teacher used picture, text and video during teaching process.Keywords : Teachers’ Teaching Strategies, Students Different Learning Style